ANALISIS PENERAPAN TAX PLANNING PAJAK PERTAMBAHAN NILAI (PPN) TERHUTANG - Ayu Zulfiani; Muhammad Arif; Rizki Filhayati Rambe (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2021)
CV Arya has an uneven amount of VAT Payable in 2020, where each tax period tends to increase quite drastically. This is because the company has not been optimized in maximizing the input tax that can be credited so that the tax to be paid is quite large. This research is expected to be able to determine the factors that cause the company's VAT payable to fluctuate every month, to find out the strategies that can still be optimized in tax planning for VAT, as well as strategy tax planning the right so that VAT efficiency can be realized. The analytical method used is described using a quantitative approach. The types of data used are primary and secondary data. The results of the study indicate that the factors that cause VAT payable are very volatile because the company has not been optimized in maximizing its input tax. In addition, several strategies that are not optimized by companies for VAT are not yet optimal in Output Tax Efficiency Invoices, Lack of efficiency by Delaying Tax planning Input Taxes with Delaying Crediting Input Taxes and still making purchase of BKP/JKP to Non PKP. As for strategy tax planning the right so that the efficiency of Value Added Tax can be realized by purchasing BKP/JKP to PKP only.